Smart Cities in Asia Regulations, Problems, and Development - Phan, Thanh; Damian, Daniela (SpringerBriefs in Geography, 2022)
This open access book examines different aspects of smart cities, including technology, urban development, sustainable development, finance, and privacy and data protection. It also covers a wide range of jurisdictions in Asia-Pacific: Hong Kong, Indonesia, Malaysia, Singapore, Thailand, and Vietnam. The book consists of two main parts. The first part includes general chapters that conceptualize smart cities and provide an overview of these cities' problems such as privacy and data protection concern. The general chapters also discuss the role of public and private sectors in developing and governing smart cities. The second part encompasses country-specific chapters that examine the concepts addressed in the general chapters in practice by analyzing several specific smart city projects. This book provides researchers and practitioners with some knowledge of a smart city and its implication in the Asia context. The book is designed with some general chapters updating the literature on smart cities for readers who are interested in an overview of this concept. Audiences who are curious about how smart cities are perceived and implemented in some Asian jurisdictions are benefited from country-specific chapters. The book is also helpful to general audiences whose interests lay at the intersection of law, governance, and technology.